Cryogenic electron tomography reconstructions from phaseless data. (4th October 2018) - Zickert, Gustav; Maretzke, Simon
Abstract: We perform three-dimensional (3D) reconstructions from simulated and real cryogenic electron tomography (cryo-ET) data. Our reconstructions are based on a nonlinear and phaseless forward model very reminiscent of a commonly used model for phase contrast x-ray tomography.